RANCANGAN BRIDGING SISTEM INFORMASI PRIMARY CARE (P-CARE) PADA DOKTER PRAKTEK DI KOTA SEMARANG - Prasetyowati, Asih; Rahadiyanto, Cahyono (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Applications P-Care (primary care) is an information system of patient care participants BPJS computer-based and online via the Internet. There are some problems encountered in the use of p-care applications in clinic. Patients who visit private doctors have not been entirely entered into BPJS participants so that there are two kinds of membership, namely patient based on the patient BPJS and general patients. Difficulties experienced was when combining patient visitation reports BPJS participants and general patients. The purpose of this study was to produce a draft bridging medical record information system that can bridge the gap between the general patient care with patients BPJS. This type of research is a case study with observational approach. Object of this research are the components ofÂ the p-care information systems. Subjects were the operators, doctors, and owners of primary health care facilities. Data collection were interviews and observations to gain condition p-care information system is running and the user's expectations for efficiency p-care services. Problems on the clinic services is the difficulty in finding the patient's medical record card, and there are multiple medical record card. Another problem is that there are patients who used the card BPJS others and create time reports that are less efficient. Solutions do is arrange medical record card with the number system, making treatment of identity cards, and establish procedures medical record service. To expedite the necessary service bridging primary care information system designed according to the needs of the clinic management information. The database that corresponds to bridging p-care are patient identity, health care visit, health service, and diagnosis. The design of the interface (interface) generated registration menu, service, and reporting. Necessary cooperation with the IT BPJS to build bridging systems for ease of service and clinical reporting